Conference Proceedings of Social Sciences Postgraduate International Seminar (SSPIS) 2015 - Bashir Ribadu, Abubakar; Uyi Ehigiamusoe, Kizito (2015)
The objectives of this seminar are: To provide an avenue for postgraduate students to present their research findings, impart knowledge and get feedback; To promote interactions among participants; To enhance networking among researchers; and To assist postgraduate students with publication opportunities.